Kinematically complete studies of collisions between simple molecular ions and neutral gas targets - Johnson, Nora Gerline (Kansas State University, 2010)
Collisions between simple diatomic molecular ions and target atoms have previously been limited to studying a subset of reaction channels for a given experiment, or, for cases where all reaction channels involved were measured, only the cross sections have been reported in literature. Experimentalists are faced with the challenge of improving their techniques for studying these collisions in order to gain further physical insight into the processes which occur. Our group has made progress in studying the molecular dissociation channels from the collisions via a coincidence three-dimensional momentum imaging technique. This technique allows us to measure all reaction channels involved simultaneously, while separating the channels from each other. By re-design of the experimental apparatus, i.e. changing the target from a gas cell to an open geometry jet, we have gained the ability to measure recoil ions produced in the collision in addition to the molecular fragments. Furthermore, we can also study collisions where the molecular projectile does not dissociate as long as it scatters to large angles. Results from the collision cell setup will be shown and discussed as well as first results from the jet setup. This work is a contribution to a larger project, and the emphasis for this stage will be placed on the development of the experimental technique as well as improvements for the future of the project.
Keywords: Collision; Physics, Molecular (0609)